Gray Matter Changes in the Insular Cortex During the Course of the Schizophrenia Spectrum - Takahashi, Tsutomu; Kido, Mikio; Sasabayashi, Daiki; Nakamura, Mihoko; Furuichi, Atsushi; Takayanagi, Yoichiro; Noguchi, Kyo; Suzuki, Michio (Frontiers in Psychiatry, 2020)
Progressive gray matter reductions in the insular cortex have been reported in the early phases of schizophrenia (Sz); however, the trajectory of these reductions during the course of the illness currently remains unclear. Furthermore, it has not yet been established whether patients with schizotypal (SzTypal) features exhibit progressive changes in the insular cortex. This follow-up magnetic resonance imaging study examined volume changes in the short and long insular cortices (mean inter-scan interval = 2.6 years) of 23 first-episode (FE) and 17 chronic patients with Sz, 14 with SzTypal disorder, and 21 healthy controls. Baseline comparisons revealed smaller insular cortex volumes bilaterally in Sz patients (particularly in the chronic group) than in SzTypal patients and healthy controls. FESz patients showed significantly larger gray matter reductions in the insular cortex over time (left: -3.4%/year; right: -2.9%/year) than those in healthy controls (-0.1%/year for both hemispheres) without the effect of subregion or antipsychotic medication, whereas chronic Sz (left: -1.5%/year; right: -1.6%/year) and SzTypal (left: 0.5%/year; right: -0.6%/year) patients did not. Active atrophy of the right insular cortex during FE correlated with fewer improvements in positive symptoms in the Sz groups, while mild atrophy of the left insular cortex during the chronic phase was associated with the severity of negative symptoms in the follow-up period. The present results support dynamic volumetric changes in the insular cortex being specific to overt Sz among the spectrum disorders examined and their degree and role in symptomatology appear to differ across the illness stages.